2019
DOI: 10.1142/s2424835519500486
|View full text |Cite
|
Sign up to set email alerts
|

Wide Awake Local Anesthesia No Tourniquet: A Pilot Study for Carpal Tunnel Release in the Philippine Orthopedic Center

Abstract: Background: Wide Awake Local Anesthesia No Tourniquet (WALANT) uses a mixture of lidocaine and epinephrine for anesthesia and has found great success in hand surgery. At the Philippine Orthopedic Center (POC), we still use local anesthesia along with a tourniquet which gives the patient pain and discomfort at the tourniquet site. This study aims to determine perioperative and post-operative pain, intraoperative bleeding and immediate clinical outcomes of patients using WALANT for surgical anesthesia for carpal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Releases performed with the standard anesthetic technique show complications in 1-25% of cases with reoperation rates of up to 12% ( Table 6 ). 50 , 51 , 52 , 53 , 54 , 55 , 56 Our study found a complication rate of 10.16 %, with a reoperation rate of 1.5 %. These differences may result from the small sample sizes used in the WALANT studies.…”
Section: Discussionsupporting
confidence: 47%
“…Releases performed with the standard anesthetic technique show complications in 1-25% of cases with reoperation rates of up to 12% ( Table 6 ). 50 , 51 , 52 , 53 , 54 , 55 , 56 Our study found a complication rate of 10.16 %, with a reoperation rate of 1.5 %. These differences may result from the small sample sizes used in the WALANT studies.…”
Section: Discussionsupporting
confidence: 47%
“…The absence of a completely bloodless operative field, otherwise afforded by a tourniquet, is generally accepted with WALANT. 25 Gunasagaran has shown no significant difference in estimated blood loss or operative time between WALANT and LA/TQ-based anesthetics. 26 Others have found that WALANT provided a better surgical field than a tourniquet for trigger finger release (TFR) amongst 86 patients.…”
Section: Resultsmentioning
confidence: 94%
“…The use of WALANT surgery is prevalent among hand surgeons. A pilot study on this was recently reported by Magtoto and Alagar 9 on their experience at a local government hospital on carpal tunnel syndrome. Although in their report, none were bloodless nor had too much bleeding, no complications were noted, and the pain was very well controlled in their 13 patients.…”
mentioning
confidence: 98%